2023
DOI: 10.21608/smj.2022.154593.1338
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline in patients of breast cancer at Sohag University Hospital

Abstract: Cognitive decline in breast cancer patients can occur treatment related or nontreatment related. Disturbance of cognition can occur before start of any cancer therapy or in association with breast cancer therapy (e.g., radiation, hormonal therapy). Risk factors include a patient's characteristics, such as psychological and genetic parameters other than the impact of cancer and cancer therapy. Incidence of cognitive disturbance in patients who receive chemotherapy is higher than patients receiving hormonal ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It strongly emphasizes sustainability initiatives and maintaining a green environment. These efforts include implementing various sustainability seminars, activities (e.g., tree planting), and programs to raise environmental awareness and ensure proper waste disposal [62]. Previous studies have indicated that students' participation in sustainable development activities positively influences their SC [51,63].…”
Section: Discussionmentioning
confidence: 99%
“…It strongly emphasizes sustainability initiatives and maintaining a green environment. These efforts include implementing various sustainability seminars, activities (e.g., tree planting), and programs to raise environmental awareness and ensure proper waste disposal [62]. Previous studies have indicated that students' participation in sustainable development activities positively influences their SC [51,63].…”
Section: Discussionmentioning
confidence: 99%